(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Mutual funds categorized as environmental, social, and governance, or ESG, invests in businesses that adhere to ESG standards and prioritize sustainable development. It makes investments in a specific field or theme, like technology, healthcare, or renewable energy. ESG funds only make investments in a business that share their commitment to social responsibility, environmental preservation, and sound corporate governance and seeks to have a positive environmental impact in addition to offering respectable financial returns.The study aims to provide a comprehensive analysis of the current status of Environmental, Social, and Governance (ESG) mutual funds in Indian prospective.This study found that the present status of ESG Mutual is fluctuating in terms of assets under management (AUM) and net inflows or outflows, But the growth pattern of this type of fund has been seen to be quite good considering its nascent date.As per SEBI guidelines, some major changes are also being seen, like six specific strategies, and equity and equity-related instruments of that specific scheme strategy must account for at least 80% of the total assets under management (AUM) of ESG schemes. The objective of this research is to help stakeholders, such as investors, fund managers, and policymakers, in making well-informed decisions by adding to the body of knowledge already available on sustainable finance. The study aims to offer actionable suggestions for the improvement of ESG mutual funds in India, promoting a more sustainable and ethical investment environment, by identifying opportunities and challenges.